(untitled) (Journal of the College of Basic Education, 2023)
In a study of the benthic invertebrate community in the Lesser Zab, Alton Kupri 1 North regionIraq, associated with the sedge plant 67/7775 6700/7145, the isolation results showed: 23 individuals fromNematodes of Genus 7700/7.,. 4, l, nh. 1, additionFor suspension. 50 10550/00707000 with numbers 23, 7, 7, 4, 5, 35, respectively. I showedThe results showed that the number of arthropods of the genera. 7715,. h,. nThey were: 95, 119, 21, respectively, and 19 individuals from Al-Nawaem, genus 4906750: 776/7,The highest percentage was for. 0100) and less than a percentage of . ,The results of relative abundance showed the dominance of the Arthropoda phylum, while the rest of the phylum were the racesLow abundance, the average hydrogen ion concentration (7.1 - 7.5) and degrees were recordedThe temperature was (16-191) degrees Celsius, while the average salinity concentration was (-.,462).).,9 thousandths.